PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS II SEKOLAH DASAR - Shiratul mustaqim; Zulfah; Moh, Fauziddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve the ability to understand mathematical concepts in class II elementary school students through the application of the Picture and Picture learning model. The background to this research is students' low understanding of mathematical concepts which is often caused by conventional learning methods that are less interesting and innovative. This classroom action research was carried out in two cycles, with each cycle including planning, implementation, observation and reflection. The research subjects were 8 class II students at SD Negeri 018 Laggini. Data was collected through learning results tests, teacher and student activity observation sheets, and interviews. The research results showed that there was a significant increase in students' understanding of mathematical concepts after implementing the Picture and Picture learning model. In the first cycle of Meeting I, the percentage of student learning completion reached 50%, and increased to 62.5% in the first cycle of Meeting II. Continues to increase in Cycle II, meeting I by 75%. In cycle II, Meeting II reached 100%. Apart from that, student learning activities become more enthusiastic and participatory. This improvement is supported by the use of relevant and systematic image media in learning, thereby helping students construct their understanding visually. Thus, it can be concluded that the Picture and Picture learning model is effective in improving the ability to understand mathematical concepts in class II elementary school students.